Cobalt and Ruthenium drift in ultra-thin oxides. (September 2019) - Tierno, D.; Varela Pedreira, O.; Wu, C.; Jourdan, N.; Kljucar, L.; Tőkei, Zs.; Croes, K.
Abstract: Cobalt (Co) and ruthenium (Ru) have been proposed for novel metallization schemes to replace copper in next generation BEOL systems that will use ultra-thin oxide layers. Using TDDB measurements performed on planar capacitors we evaluated the performances of the two metals: both CVD Co and CVD Ru are affected by metal drift, differently to previously reported results for ALD and PVD Ru that showed no sign of metal drift. We believe that not oxide scaling, but the deposition conditions used for our CVD process are responsible for the different behaviour of Ru. In particular, the CVD precursors used for Ru deposition lead to the incorporation of impurities that made the Ru bonds easier to break and thus CVD Ru is more susceptible to ionization processes occurring at the metal/dielectric interface. Moreover, our data show also an impact of the SiO2 deposition technique on these processes because PECVD and PEALD lead to different oxide surface conditions. Finally, an increase in acceleration factor was observed at low field values for both Co and Ru, as predicted by the filament formation and growth model, confirming the need to test BEOL systems in a wide range of test conditions for reliable lifetime estimations. Highlights: Metal drift induced failure is observed in MIM capacitors mimicking advanced BEOL systems with CVD Co and CVD Ru. Deposition conditions are responsible for metal drift in barrierless Ru/SiO2 systems. TDDB data confirm the validity of the filament formation and growth model. A wide range of test conditions are needed to properly asses metal drift induced failure.